Methodology for the participation of small farmers in the design of on-farm trials - Ashby, Jacqueline A. (1986)
Although farmer participation is an important concept in farming systems programs, farmer participation is typically restricted to the management of on-farm trials and little information exists on alternative approaches. This paper evaluates three approaches to farmer participation differentiated by the extent to which farmers participated in defining criteria for the design of on-farm fertilizer trials. The three methodologies are described, and the resultant experimental designs are compared in terms of their criteria for testing fertilizers under small farm conditions. The results show that increased scope for farmer participation produced significant changes in the design of on-farm trials due to important insights into how farmers themselves would evaluate fertilizers, and raised basic research questions about improvements in the technology. The paper concludes that farmer participation in experimental design for on-farm trials requires fewer resources and less time than diagnostic survey research while qualitatively improving feedback between scientists and farmers.